Head cases eaudiobook A novel. - McMahon, John (Macmillan Audio, 2025)
Head Cases follows an enigmatic group of FBI agents as they hunt down a murderer seeking his own justice in this electrifying—and commercial—series debut. FBI Agent Gardner Camden is an analytical genius with an affinity for puzzles. He also has a blind spot on the human side of investigations, a blindness that sometimes even includes people in his own life, like his beloved seven-year-old daughter Camila. Gardner and his squad of brilliant yet quirky agents make up the Patterns and Recognition (PAR) unit, the FBI's hidden edge, brought in for cases that no one else can solve. When DNA links a murder victim to a serial killer long presumed dead, the team springs into action. A second victim establishes a pattern, and the murderer begins leaving a trail of clues and riddles especially for Gardner. And while the PAR team is usually relegated to working cold cases from behind a desk, the investigation puts them on the road and into the public eye, following in the footsteps of a killer. Along with Gardner, PAR consists of a mathematician, a weapons expert, a computer analyst, and their leader, a career agent. Each of them must use every skill they have to solve the riddle of the killer's identity. But with the perpetrator somehow learning more and more about the team at PAR, can they protect themselves and their families...before it's too late? With an enigmatic case that will keep readers on the edge of their seats and a thoroughly engaging ensemble cast, John McMahon's Head Cases is a triumph. A Macmillan Audio production from Minotaur Books.